An Analysis of the effect of gender equality on peace consolidation in Zmbabwe from 1980 to 2017. - Zhandire, Nyaradzo (Midlands State University, 2020)
The research explored analysed the effects of gender equality on peace consolidation within Zimbabwe from the post-independence period till 2017. The waves of democracy and different feminist theories being explored at all levels within a state have given rise to the involvement of women in political processes such as peace consolidation. The inclusion of women in policy formulation and decision making processes has been greatly advocated for especially when it comes to peace processes. The research looked at the challenges faced by women in Zimbabwe when it came to participating in political processes especially in a society that is pre-dominantly patriarchal. It also looked at measures and progress taken so far by state and non-actors and placed recommendations to be taken in order to fast track peace consolidation in holistic manner through gender equality. Data was collected and analysed qualitatively using questionnaires and in-depth interviews which gave a viable explanation as to people’s feelings toward gender equality and what effect it could have on peace consolidation in the future. Graphs, tables and pie charts were used to outline the findings of the research that were give an indication of whom and how many people within a selected group were aware of gender equality and its effects and how many supported the linkage between gender equality and political participation. Furthermore, the in-depth interviews and questionnaires gave a broader and deeper understanding as to the varying numbers and percentages in the graphs and charts.